Predictability of the psychological impact of the economic crisis on family functioning within the family context in Sri Lanka - Uditha, Sasini; Bulathwatta, Asanka (Frontiers in Psychology, 2025)
IntroductionThe financial crisis due to COVID-19 and other socio-political constraints led to family vulnerability, leading to psychological disorders that disrupt individual well-being and family dynamics and relationships. Researchers emphasize the importance of predicting and mitigating these psychological effects to avoid long-term adverse outcomes. The main objectives were to understand the factors contributing to family resilience and the psychological impact of financial hardship on family functioning in the Sri Lankan context.MethodsThis study examined whether the economic crisis impacts family functioning within the family context. The participants received a questionnaire comprising four subsections to collect quantitative data. The first section was for informed consent, and the second was for demographic-related questions. Section three was about Walsh family resilience, 32 scales. The fourth section comprised self-structured questions. Participants were asked to answer all these questions. The research study targets families in the Mavathalandha Grama Niladhari Division, Rathnapura district, Sri Lanka. Sample size of 100 families were selected using a stratified sampling method. The Statistical Package for Social Sciences version 22 was used to analyze and interpret data.ResultsThe study’s regression analysis results helped identify some resilience factors that directly and indirectly impact the economic crisis on family functioning within the family context. Also, in the comparative analysis of studies on family resilience, the research findings revealed the factors contributing to family resilience and the psychological impact of financial hardship on family functioning within the family context during the economic crisis.DiscussionThese findings highlight the significance of family belief systems, positive communication, and adaptive problem-solving as key components of family resilience during economic and psychological stress to provide insights into effective strategies for supporting family well-being during times of economic hardship.